Do pre-hospital physicians improve mortality in major trauma patients? A systematic review. (January 2021) - Morgan, Owen; Yarham, Eilish; Hudson, Anthony; Cole, Elaine
Background: Optimal pre-hospital care systems contribute to improvements in trauma survival. The presence of pre-hospital physicians (PHPs) is reported to increase survival in traumatic brain injury, yet the effects of PHPs on outcomes for all trauma patients is currently unreported. The objective of this systematic review was to compare trauma mortality for patients treated by a PHP with those treated by a non-medical pre-hospital practitioner (NMPHP). Methods: A systematic literature search (Medline, Embase, and CINAHL) was performed, on 10th March 2020, to identify original studies comparing the mortality for trauma patients treated by a PHP with those treated by a NMPHP published between 1st January 2010 and 31st December 2019. Methodological quality of studies was assessed using Grade of Recommendations, Assessment, Development and Evaluation (GRADE). Results: The search revealed 6, 296 studies and 14 met the inclusion criteria, comprising a total of 42, 479 patients. Unadjusted mortality suggested a higher mortality for the physician cohort in four studies and no difference in six. However, patients treated by physicians had higher Injury Severity Scores and where adjusted mortality was provided several studies showed a mortality benefit for physicians. Conclusion: This systematic review did not demonstrate a mortality benefit from pre-hospital physicians attending major trauma patients. However, those with higher Injury Severity Scores may benefit from the presence of a PHP. Identifying this patient cohort in the pre-hospital setting to ensure appropriate resource use requires further evaluation.